ASTROCYTE RESPONSE TO INTRACEREBRAL HEMORRHAGE IN VARIOUS BRAIN REGIONS AND PHARMACOLOGICAL CORRECTION - Kuraieva, A.V.; Savosko, S.I.; Grabovyi, A.N.; Makarenko, O.M. (World of Medicine and Biology, 2023)
Astrogliosis is a typical astrocyte response to intracerebral hemorrhage. The purpose of the study was to analyze morphological changes in astrocytes in the cerebral cortex, hippocampus, and striatum of rats with intracerebral hemorrhage and after administration of dexamethasone, granulocyte colony-stimulating factor and their combination. Astrocyte morphology, changes in projection perimeter and their density on days 1, 3, 10, 30 and 60 in three brain regions were studied based on the results of immunohistochemical staining for glial fibrillary acidic protein in astrocytes. Dexamethasone stimulated astrocyte hypertrophy in the cerebral cortex on days 3 and 10, and the granulocyte colony-stimulating factor caused an increase in astrocyte density on day 3 of the study. The morphological features of astrocyte response in the study regions of the brain were different: active hypertrophy and gliosis in the striatum, and predominantly hypertrophy of processes in the cerebral cortex and hippocampus.
Keywords: intracerebral hemorrhage; astrocytes; dexamethasone; granulocyte colony-stimulating factor